Gene Polymorphisms in FAS (Rs3740286 and Rs4064) Are Involved in Endometriosis Development in Brazilian Women, but not those in CASP8 (rs13416436 and rs2037815) - Pissetti, Cristina Wide; Tanaka, Sarah Cristina Sato Vaz; Hortolani, Andrezza Cristina Cancian; Marqui, Alessandra Bernadete Trovó de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective The present study aims to investigate the association between caspase-8 (CASP8) (rs13416436 and rs2037815) and Fas cell surface death receptor (FAS) (rs3740286 and rs4064) polymorphisms with endometriosis in Brazilian women.Methods In the present case-control study, 45 women with a diagnosis of endometriosis and 78 normal healthy women as a control group were included. The genotyping was determined by real-time polymerase chain reaction (PCR) with Taqman hydrolysis probes (Thermo Fisher Scientific, Darmstadt, Germany). Genotypic and allelic frequencies were analyzed using Chi-squared (χ2) test. In order to determine the inheritance models and haplotypes ,SNPStats (Institut Català d'Oncologia, Barcelona, Spain) was used. Levels of 5% (p = 0.05) were considered statistically significant.Results No significant difference was observed in genotypic or allelic frequencies between control and endometriosis groups for rs13416436 and rs2037815 (CASP8 gene). On the other hand, a significant difference between rs3740286 and rs4064 (FAS gene) was found. Regarding polymorphisms in the FAS gene, a statistically significant difference was found in co-dominant and dominant models. Only the haplotype containing the rs3740286A and rs4064G alleles in the FAS gene were statistically significant.Conclusion The polymorphisms in the CASP8 gene were not associated with endometriosis. The results indicate an association between FAS gene polymorphisms and the risk of developing endometriosis.
Keywords: endometriosis; apoptosis; genetic polymorphism; real-time polymerase chain reaction; genetic predisposition to disease